Marking Meaning: EFL students’ Annotation as a Tool for Academic Literacy - Vonti, Lungguh Halira; Andovita, Leora Grahadila; Aslamiyah, Susi; Herawati, Atti (English Education:Journal of English Teaching and Research, 2025)
In the context of Indonesia higher education, English academic reading poses notable challenges for EFL students, particularly due to complex language and limited instructional support. To address this issue, annotation emerges as a critical strategy to facilitate comprehension and engagement with scholarly texts. This study aims to explore the annotation practices employed by eight-semester EFL students when reading academic materials. Using a descriptive qualitative method, data were collected through documentation of annotated texts and semi-structured interviews involving six students from an English Language Education Study Program at Pakuan University. The analysis followed Marshall's framework, categorizing annotations into three types: anchor only, content only, and compound. Findings revealed that students predominantly used anchor only annotations-highlighting and underlining- to mark essential information. Some employed compound annotations by integrating text markers with reflective notes, while content only annotations were less frequent but demonstrated deeper processing through independent summaries. These practices indicate that annotation supports not only reading comprehension but also academic writing and critical engagement. The study recommends integrating explicit instruction on annotation techniques into EFL reading curricula to empower students as active readers and knowledge constructors.